N-Terminal Pro-B-Type Natriuretic Peptide in Risk Stratification of Heart Failure Patients With Implantable Cardioverter-Defibrillator - Deng, Yu; Cheng, Si-Jing; Hua, Wei; Cai, Min-Si; Zhang, Ni-Xiao; Niu, Hong-Xia; Chen, Xu-Hua; Gu, Min; Cai, Chi; Liu, Xi; Huang, Hao; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2022)
Background: Prognostic value of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in heart failure is well-established. However, whether it could facilitate the risk stratification of heart failure patients with implantable cardioverter-defibrillator (ICD) is still unclear. Objective: To determine the associations between baseline NT-proBNP and outcomes of all-cause mortality and first appropriate shock due to sustained ventricular tachycardia/ventricular fibrillation in ICD recipients. Methods and Results: NT-proBNP was measured before ICD implant in 500 patients (mean age 60.2±12.0 years; 415 (83.0%) male; 231 (46.2%) non-ischemic dilated cardiomyopathy; 136 (27.2%) primary prevention). The median NT-proBNP was 854.3 pg/mL (interquartile range: 402.0 to 1817.8 pg/mL). We categorized NT-proBNP levels into quartiles and used a restricted cubic spline to evaluate its nonlinear association with outcomes. The incidence rates of mortality and first appropriate shock were 5.6% and 9.1%, respectively. After adjusting for confounding factors, multivariable Cox regression showed a rise in NT-proBNP was associated with an increased risk of all-cause mortality. Compared with the lowest quartile, the hazard ratios with 95% confidence interval across increasing quartiles were 1.77 (0.71, 4.43), 3.98 (1.71, 9.25), and 5.90 (2.43, 14.30) for NT-proBNP (P for trend < 0.001). Restricted cubic spline demonstrated a similar pattern with an inflection point found at 3231.4 pg/mL, beyond which the increase in NT-proBNP was not associated with increased mortality (P for nonlinearity < 0.001). Fine-Gray regression was used to evaluate the association between NT-proBNP and first appropriate shock accounting for the competing risk of death. In the unadjusted, partial, and fully adjusted analysis, however, no significant association could be found regardless of NT-proBNP as a categorical variable or log-transformed continuous variable (all P > 0.05). No nonlinearity was found, either (P = 0.666). Interactions between NT-proBNP and predefined factors were not found (all P > 0.1). Conclusion: In heart failure patients with ICD, the rise in NT-proBNP is independently associated with increased mortality until it reaches the inflection point. However, its association with first appropriate shock was not found. Patients with higher NT-proBNP levels might derive less benefit from ICD implant.